Physical and Chemical Characteristics of Mangos (Mangifera indica L.) during Storage with Various Methods of Packaging - Merynda Indriyani Syafutri; Filli Pratama; Daniel Saputra (Jurnal Teknologi dan Industri Pangan, 2006)
The research was aimed to determine the physical and chemical characteristics of mangos in various packing methods during storage. Factorial Completely Randomized Design with four treatments and three replications were used in this research. The treatments were individually and collectively packed mangos which were stored at 10 and 200C. The physical and chemical changes of mangos in the flexible packaging (individual and collective) were slower than mangos without packaging. Collectively packed mango stored was with the storage temperature of 100C was found to have longer shelf life than that of other treatments. On day 25, the collectively packed mango had weight loss of 1,464%, 0,316 Kgf hardness, 11,4% total sugars, 0,44% total acids, and 229,44 mg/100g vitamin C. Further duo-trio test indicated that panelists could detect the differences of the taste between packed and freshly harvested mangos. The hedonic test shows that most panelists preferred the taste of mangos that were collectively packed and stored at 100C (on day 10). Key words: Mangos, method, packaging, storage